Le duc de Blacas (1771-1839) en Italie : les grandes étapes dans la constitution d’une collection privée au début du XIXe siècle - Camille Py (Les Cahiers de l'École du Louvre)
The Duc de Blacas is as important but forgotten figure in the history of collecting. A convinced legitimist, he joined the conservative camp even though the first quarter of the nineteenth century was marked by the legacy of the revolution. His growing unpopularity, repeated exiles and, finally, the sale of his collection to the British Museum in 1866 contributed to his relative oblivion. However, during his various trips to the Italian peninsula, the Duc de Blacas proved to be an open-minded collector, helped by his involvement in various Florentine, Roman and Neapolitan social circles. His links with European monarchies gradually provided him with the means to serve his passion for antiquity as well as his interest in his contemporaries. The resulting collection reflects both the duke’s personal convictions and his integration into Italian artistic, intellectual and mercantile circles in the early nineteenth century.